2001
DOI: 10.1038/35081514
|View full text |Cite
|
Sign up to set email alerts
|

Roles of serine/threonine phosphatases in hippocampel synaptic plasticity

Abstract: REVIEWSConsider a busy Manhattan street. Cars and people moving from store to store, apartment to place of business, leaving behind their tyre tracks, coffee cups, oil spills and so on. This rubbish is then steadily cleaned away by street sweepers and janitors. A common school of thought in neuroscience has been much in the same vein -kinases moving from protein to protein within the dendritic spine or presynaptic terminal, phosphorylating these proteins and changing their function, while phosphatases work beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
266
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(274 citation statements)
references
References 112 publications
(126 reference statements)
8
266
0
Order By: Relevance
“…Serine/threonine protein phosphatases have been implicated in the regulation of synaptic plasticity [70]. A possible role for adenosine in synaptic plasticity is not adequately appreciated given that regulation of extracellular adenosine levels may have important effects in paradigms used to demonstrate plasticity.…”
Section: Adenosine In Ltp and Ltdmentioning
confidence: 99%
See 1 more Smart Citation
“…Serine/threonine protein phosphatases have been implicated in the regulation of synaptic plasticity [70]. A possible role for adenosine in synaptic plasticity is not adequately appreciated given that regulation of extracellular adenosine levels may have important effects in paradigms used to demonstrate plasticity.…”
Section: Adenosine In Ltp and Ltdmentioning
confidence: 99%
“…Kinases play important, well documented, roles in the regulation of numerous cellular functions [10,43,67]. The physiological significance of serine/threonine protein phosphatases has also been appreciated, and these enzymes have been implicated in the regulation of ion channels, synaptic plasticity, exocytosis, and apoptosis [31,36,58,70].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activity of CaN in CA1 neurons of the hippocampus is increased by activation of NMDA receptors (Lu et al, 2000). Also, there is extensive evidence showing that CaN plays a critical role in the activitydependent changes of excitatory synaptic transmission in the hippocampus (Winder and Sweatt, 2001). Genetic inhibition of endogenous CaN in the forebrain (CaN transgenic mice), by expressing the auto-inhibitory domain of CaN, showed that LTP at CA1 excitatory synapses induced by subsaturating but not saturating tetanic stimulation was enhanced both in vitro and in vivo (Malleret et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…When activated by calcium and calmodulin, calcineurin dephosphorylates target proteins such as synapsin I, DARPP32, and CREB, as well as a number of other proteins important for neuronal function including calcium channels, alpha-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptors, and N-methyl-D-aspartate (NMDA) receptors (Greengard et al 1999;Jovanovic et al 2001;Winder and Sweatt 2001). Thus, calcineurin activity could modulate cocaine-mediated neurotransmitter release and intracellular signaling through actions at several different pre-synaptic and postsynaptic targets.…”
Section: Introductionmentioning
confidence: 99%